Physiological variables to use in the gender comparison in highly trained runners - Maldonado-Martin, S.; Mujika, I.; Padilla, S. (The Journal of Sports Medicine and Physical Fitness, 2004)
Aim: The aims of this investigation were to compare physiological characteristics between highly trained middle-distance and marathon male (n=17) and female (n=11) runners; to determine the most suitable variables to use in the gender comparison in these subjects, considering physical difference between genders; and to indicate some of the best predictors of performance in running events in which oxidative metabolism prevails. Methods: Subjects performed a progressive maximal exercise on the treadmill to determine maximal oxygen uptake (VO2max) and velocities corresponding to a blood lactate concentration of 4 mmol · l-1 (uOBLA) and to the lactate threshold (uLT). Cost of running (Cr) and maximal aerobic velocity (ua max) were calculated from VO2 measurements. Results: Males presented higher VO2max, ua max, uOBLA, uLT, and VO2 @ uOBLA and uLT (p<0.001), but females had higher uOBLA and uLT (p<0.01) expressed as %VO2max. ua max correlated with performance time relative to the world record in both, females (r=-0.77, p<0.01) and males (r=-0.58, p<0.05); and uLT with performance only in males (r=-0.59, p<0.05). Conclusion: In conclusion, female athletes seemed to compensate partly their aerobic profile with higher %VO2max @ uOBLA and uLT, suggesting that both maximal and submaximal physiological variables should be considered when evaluating and comparing highly trained athletes of both genders. ua max is one of the best predictors of performance in running events in which oxidative metabolism prevails.